Sit and chat with me! An insight into the elderly - Salleh, Che Ibrahim; Abd Rahim, Normaliza; Sujud, Arbaie; Nik Affendi, Nik Rafidah (Journal of the World Universities Forum, 2009)
Everyone in the world needs someone to talk to and somebody to be there all the time. This scenario seems to be different for the elderly in Malaysia although Malaysia has taken the problems of the elderly as the first priority of humanism. The National Welfare Policy (1990) identified older persons under one of its many target groups. The policy, however, was more welfare-oriented rather than development-oriented. It was only in 1995 that the policy for the elderly was formulated to cater for the developmental needs of the older population. Therefore the objectives of the present study are to investigate the content of discussion between the elderly and the researcher and to find out their feelings and emotions while chatting. Three elderly from a government home for the elderly in Malaysia participated in this study. The study was done for two hours daily in three weeks. The conversations were taped and analyzed by using the pragmatic approach. Selected conversations were chosen for the purpose of this study. It is found that the elderly needed somebody to chat with and the chatting was actually made them moved on with their lives. This study is a research based paper to encourage university lecturers to experience community service with the elderly and at the same time be with them in order to understand and have a feel about their lives.